Pengembangan Materi Ajar Buku Saku Pada Keterampilan Menulis Puisi Berbasis Lingkungan Dan Budaya Lokal Sumatera Utara Di Kelas X - Samosir, Karnila Novita; Hanum, Inayah (STAI Denpasar Bali, 2023)
This study aims to determine the process of developing and feasibility of pocket book teaching materials on poetry writing skills based on the environment and local culture developed for class X students of SMA N 17 Medan. The subjects in this study were validators and students and the object of this study was a pocket book entitled